Evaluation of the Neuroprotective Effects of Methylprednisolone and Surgical Decompression in a Rodent Model of Traumatic Optic Neuropathy. (4th March 2022) - Korn, Philippe; Gellrich, Nils-Claudius; Spalthoff, Simon; Jehn, Philipp; Eysel, Ulf T.; Zerfowski, Martin
ABSTRACT: Purpose of the study: Traumatic optic neuropathy (TON) is a rare but serious consequence of head injuries. The optimal therapy for TON remains controversial, and standardized recommendations are lacking. The most common therapies used are steroid administration and surgical decompression procedures. The aim of the present study was to compare two common conservative and surgical therapies in a rodent model with a standardized traumatic optic nerve lesion. Materials and Methods: This study employed 59 male Wistar rats. After exposing the optic nerve, defined trauma was exerted on the optic nerve using a micromanipulator to trigger TON. Rats received either "megadose" methylprednisolone applied perioperatively or decompression via nerve sheath fenestration. The number of neurons was histologically evaluated in retinae explanted as whole mounts. Neuronal size was determined histomorphometrically. Results: Neuronal loss was significantly lower following perioperative "megadose" steroid therapy ( p = .017), especially in the central retinal area ( p = .025). Compared to the control group without therapy, on average more than 400 neurons/mm 2 were saved. In the central retinal area, more than 600 neurons/mm 2 were rescued. In contrast, neuronal loss was not significantly affected by surgical decompression; however, this procedure was associated with a reduction in neuron size ( p = .003). Conclusions: The present model revealed significant neuroprotective effects following administration of methylprednisolone for TON treatment. Mitigation of neuronal loss may result in functional benefits. Neuroprotective effects were not observed following surgical therapy, suggesting that this approach should be reserved for individual cases such as hematomas in the area of nerve envelopes.